Validation protocols for blood pressure measuring devices in the 21st century. Issue 7 (13th July 2018) - Stergiou, George S.; Alpert, Bruce S.; Mieke, Stephan; Wang, Jiguang; O'Brien, Eoin
Abstract : Blood pressure (BP) is a vital sign and the essential measurement for the diagnosis of hypertension. Therefore, its accurate measurement is a key element for the evaluation of many medical conditions and for the reliable diagnosis and efficient treatment of hypertension. In the last 3 decades prestigious organizations, such as the US Association for the Advancement of Medical Instrumentation (AAMI), the British Hypertension Society, the European Society of Hypertension (ESH) Working Group on BP Monitoring, and the International Organization for Standardization (ISO), have developed protocols for clinical validation of BP measuring devices. All these initiatives aim to standardize validation procedures and establish minimum accuracy standards for BP monitors. Unfortunately, only a few of the BP measuring devices available on the market have been subjected to independent validation using one of these protocols. Recently, the AAMI, ESH, and ISO experts agreed to develop a single universally acceptable standard (AAMI/ESH/ISO), which will replace all previous protocols. This major international initiative has been undertaken to best serve the needs of patients with hypertension, a public interested in cardiovascular health, practicing physicians, scientific researchers, regulatory bodies, and manufacturers. There is an urgent need to influence regulatory authorities throughout the world to make it mandatory for all BP measuring devices to have undergone independent validation before approval for marketing. Efforts need to be intensified to improve the accuracy of BP measuring devices, further optimize the validation procedure, and ensure that objective and unbiased validation data become available.